Self-care Management in Heart Failure Using Roy Adaptation Theory-guided Intervention in the United Arab Emirates - Soufiane Roussia RN-BSN, MSN; Priyalatha Muthu RN, PhD; Rose Ekama Ilesanmi RN, PhD, FWACN, IIWCC (Stellenbosch) (SAGE Publishing, 2023)
Purpose To assess the knowledge and practice of self-care management among patients with heart failure (HF) after Roy adaptation theory-guided educational program. Methodology One group quasi-experimental pretest-posttest design of 30 purposively selected patients with HF was conducted. Outcomes were examined under three domains: knowledge, self-care maintenance, and monitoring pre- and post-intervention, using a validated instrument based on four adaptive modes of Roy's theory. Major results Most of the respondents were male (76.6%) and 56.7% were over 60 years of age. At the pretest, only 16.7% demonstrated adequate knowledge of self-care, and 76.7% reported poor practices in the domains of self-care maintenance and monitoring. Also, 90% scored poorly in self-care management. Knowledge of self-care practices increased at post-test (93.3%). There was a significant difference in knowledge ( t  = 15.79, df = 29, p  < .001) and practice ( t  = 9.35, df = 29, p  < .001) pre- and post-intervention. However, there was no significant association between selected demographic characteristics, knowledge, and self-care practice ( p  > .05). Conclusion Knowledge and practice of self-care management are poor among patients with HF. However, theory-driven practice can enhance care and patients' quality of life.